PENGARUH KUALITAS INFORMASI AKUNTANSI MANAJEMEN DAN KUALITAS MANAJER DALAM PENGAMBILAN KEPUTUSAN TERHADAP KINERJA KEUANGAN RUMAH SAKIT (Studi Pada Rumah Sakit Umum di Kotamadya Bekasi) - Wiwi Idawati (Jurnal Akuntansi Bisnis, 2017)
The purpose of this research is to identify: (1) whether  the management accounting information quality of manager influence the decision making at public hospital in municipality of bekasi, and (2) whether decision making influence financial performance at public hospital in municipality of bekasi. The population of this research  are all of public hospitals in municipality of bekasi, including those who owned  by state and private. This research is conduct with cencus approach. Distribution and filling the questioner and interview were used to collect the data. The hypothesis of this research are:       (1) accounting information quality and quality of manager influence the dicision making at public hospital in municipality of bekasi positively, and (2) the dicision making influence financial performance at public hospital in municipality of bekasi positively, these meet with data gathered from participant and then it was processed by using double linear regression analysis model.  The result of this research shows that both of the management accounting information quality and quality of manager have positive influence on decision making simoutltantly. The decision making has positive influence on financial performance of public hospital in municipality of bekasi.Key Word: Management accounting information quality, quality of manager,                        decision making, and financial performance.